PENGARUH PERLINDUNGAN KERAHASIAAN REKAM MEDIS TERHADAP STANDAR AKREDITASI KLINIK 3.4. DI KLINIK PRATAMA LUHUR MEDICA CENTRE CIMAHI - Sali Setiatin; Tiara Kusumawardani; Leni Herfiyanti (INFOKES (Informasi Kesehatan), 2020)
This research aims to know the influence of medical record confidentiality protection against clinic accreditation standards 3.4. at Pratama Luhur Medica Centre Clinic Cimahi. The research Method used are quantitative research with descriptive approach. Data collection techniques used are by way of observation, questionnaires and studies of the literature. Based on a simple linear regression test results with the number of samples of n = 6 respondents and significant α = 0.1 confidence level of 90% with the influence of 99.2% of the variable and medical record confidentiality protection 0.8% is affected by other variables. The problems was found are : (1) Not yet available regulation and policies about the privacy of medical record, (2) File medical record storage shelves are still mixed with other things, (3) Storage space is still fused with other rooms such as the living room, (4) Not yet safeguards door to access medical record file storage space, (5) CCTV is not focus to medical record storage space (6) There are medical records are missing, (7) There are medical records are broken. As for the advice given to these problems : (1) Create policies and procedure standards operational related to medical record confidentiality, (2) Employee lockers provided, (3) Create a special room or given medical record delimiter between room, (4) Installing a finger print or access code on the entrance of storage space, (5) Addition of CCTV on entrance door and storage space, (6) Provision of tracer for mark to medical record that come out, (7) Create folders to minimize damaged medical records